Tumor‐Selective Nano‐Dispatcher Enforced Cancer Immunotherapeutic Effects via Regulating Lactate Metabolism and Activating Toll‐Like Receptors - Liu, Yang; Li, Hui; Hao, Yan‐Yun; Huang, Ling‐Ling; Li, Xia; Zou, Jing; Zhang, Shi‐Ying; Yang, Xiao‐Yue; Chen, Hong‐Fei; Guo, Yi‐Xuan; Guan, Yun‐Yan; Zhang, Zhi‐Yue (Small (Weinheim an der Bergstrasse, Germany), 2025)
The development of tumors relies on lactate metabolic reprogramming to facilitate their unchecked growth and evade immune surveillance. This poses a significant challenge to the efficacy of antitumor immunity. To address this, a tumor‐selective nano‐dispatcher, PIMDQ/Syro‐RNP, to enforce the immunotherapeutic effect through regulation of lactate metabolism and activation of toll‐like receptors is developed. By using the tumor‐targeting properties of c‐RGD, the system can effectively deliver monocarboxylate transporters 4 (MCT4) inhibitor (Syro) to inhibit lactate efflux in tumor cells, leading to decreased lactate levels in the tumor microenvironment (TME) and increased accumulation within tumor cells. The reduction of lactate in TME will reduce the nutritional support for regulatory T cells (Tregs) and promote the effector function of T cells. The accumulation of lactate in tumor cells will lead to tumor death due to cellular acidosis. In addition, it will also reduce the uptake of glucose by tumor cells, reduce nutrient plunder, and further weaken the inhibition of T cell function. Furthermore, the pH‐responsive release of Toll‐like receptors (TLR) 7/8 agonist IMDQ within the TME activates dendritic cells (DCs) and promotes the infiltration of T cells. These findings offer a promising approach for enhancing tumor immune response through targeted metabolic interventions. The development of tumors can result in increased lactate production and immunosuppression. The overexpression of MCT4 in tumors results in excessive lactate efflux, contributing to elevated lactate levels. A tumor‐selective system (PIMDQ/Syro‐RNP) allows for the simultaneous delivery of MCT4 inhibitor (Syro) and TLR7/8 agonist (IMDQ). The PIMDQ/Syro‐RNP has shown efficacy in reducing lactate efflux, activating DCs, and improving immunotherapy.